Maqāma as Small/Minor Literature in Nigeria - Alagunfon, Sulaiman Adewale (Rocznik Orientalistyczny/Yearbook of Oriental Studies, 2026)
In this paper, I explore the development of Arabic language in Nigeria across different historical dimensions and its implications for the intellectual production of those scholars who use it for literary purposes today. Arabic, as one of the prominent languages in Nigeria, continues to serve as an important medium for education, scholarship, and erudition, despite not receiving official recognition. I focus on the recent evolution of the maqāma (pl. maqāmāt) as a result of the enduring Arabic literary tradition, particularly influenced by classical maqāma works such as Maqāmāt Al-Ḥarīrī. I investigate how the knowledge and writings of Arabic literature have enabled “Arabists” in Nigeria to redefine their literary positionality within the national literary landscape. Additionally, I examine to what extent their Arabic works, particularly their maqāma; conform to the concepts of “minor” or “small” literature, drawing on the analyses of Gilles Deleuze and Félix Guattari regarding Franz Kafka and Pascale Casanova’s interpretations of the concept.